A systematic approach to map the adolescent human papillomavirus vaccine decision and identify intervention strategies to address vaccine hesitancy. (December 2019) - Marshall, S.; Sahm, L.J.; Moore, A.C.; Fleming, A.
Abstract: Objectives: Unsubstantiated safety concerns with human papillomavirus (HPV) vaccines continue to linger. This study sought to identify factors that influence the adolescent HPV vaccine decision and systematically identify intervention functions and strategies likely to be effective in reducing vaccine hesitancy. Study design: This is a qualitative focus group study. Methods: Focus groups were conducted with female adolescents (aged 14–16 years) in Cork and Kerry. During focus groups, the trained facilitator used a semistructured, Theoretical Domains Framework (TDF)–based topic guide to prompt discussion. Transcripts were thematically analysed using the TDF and Behaviour Change Wheel. Behaviour Change Technique Taxonomy version 1 was used to suggest intervention functions and strategies for addressing HPV vaccine hesitancy. Results: A total of 50 adolescents (96% vaccinated), participated in 10 focus groups. The key themes were presented by means of the relevant TDF domains. Seven domains were selected as the most relevant: knowledge, social influences, beliefs about capabilities, optimism, beliefs about consequences, emotion and environmental context and resources. Five intervention functions were identified, education, persuasion, enablement, modelling and environmental restructuring, and linked to 11 relevant Behaviour Change Technique (BCTs). Potential intervention strategies were developed. Conclusions: This study provided a detailed insight into behavioural factors influencing the vaccine decision-making process. It was identified that awareness and knowledge about HPV and its health sequelae was low. Lack of information is a well-recognised determinant of vaccine hesitancy. Therefore, education was recommended as a key area to address in future intervention studies. Highlights: The World Health Organization has declared vaccine hesitancy as one of the top ten threats to global health in 2019. Unsubstantiated safety concerns with human papillomavirus (HPV) vaccines continue to linger globally. Theoretically informed behaviour change frameworks can be used to identify factors impacting HPV vaccine uptake. Awareness and knowledge about HPV and its health sequelae was low among female adolescents, aged 14-16 years. Education is a key area to address in future intervention studies to reduce HPV vaccine hesitancy.